Conceptualizing Peasants’ Property Rights over Land under the FDRE Constitution - Chane, Gizachew Silesh (Bahir Dar University Journal of Law, 2023)
The question of who can use what resources of the land remained one of the most contentious subjects in policy debates and constitutional design. The FDRE Constitution has put in place a property regime acknowledging, inter alia, the State, the peoples of Ethiopia, peasants and pastoralists as having recognized interests/rights over land. Yet the reaches and limits of entitlements of these various stakeholders have not been resolved with a degree of certainty. This article examined the entitlements of peasants pertaining to land, based on doctrinal research method where the contents of Constitutional rules are exposed in light of general principles and concepts in property law. From this examination, it is concluded that while the letters of subsidiary laws and general rhetoric espouse the view that all potential powers and/or rights are put in the bucket of ownership and exclusively vested to the state, a closer look into the Constitutional provisions demonstrates that the state remained with a vacuum title in relation to land allocated to peasants and pastoralists individually or communally.